Sortase-mediated ligation of PsaE-modified photosystem I from Synechocystis sp. PCC 6803 to a conductive surface for enhanced photocurrent production on a gold electrode - Le, Rosemary K (Langmuir : the ACS journal of surfaces and colloids, 2015)
Sortase-mediated ligation was used to attach the photosystem I (PSI) complex from Synechocystis sp. PCC 6803 in a preferential orientation to enhance photoinduced electron flow to a conductive gold surface. Ideally, this method can result in a uniform monolayer of protein, covalently bound unidirectionally to the electrode surface. The exposed C-termini of the psaE subunits of the PSI trimer were targeted to contain an LPETG-sortase recognition sequence to increase noncompeting electron transfer by uniformly orienting the PSI stromal side proximal to the surface. Surface characterization with atomic force microscopy suggested that monolayer formation and optimal surface coverage occurred when the gold surfaces were incubated with peptide at 100 to 500 μM concentrations. When photochronoamperometry with potassium ferrocyanide and ferricyanide as redox mediators was used, photocurrents in the range of 100 to 200 nA/cm(2) were produced, which is an improvement over other attachment techniques for photosystem monolayers that produce approximately 100 nA/cm(2) or less. This work demonstrated that sortase-mediated ligation aided in the control of PSI orientation on modified gold surfaces with a distribution of 94% stromal side proximal and 6% lumenal side proximal to the surface for current-producing PSI